Ski boot canting adjustments affect kinematic, kinetic, and postural control measures associated with fall and injury risk. Issue 10 (October 2021) - Wilson, Sarah A.; Dahl, Kimi D.; Dunford, Kristin M.; Foody, Jacqueline N.; Zandiyeh, Payam; Turnbull, Travis Lee; Tashman, Scott
Abstract: Objectives: The aim of this study was to investigate if and to what extent small lateral wedges inserted under the ski boot, known as canting, could impact knee kinematics/kinetics, balance, and neuromuscular activity in recreational alpine skiers in the laboratory setting. Design: Experimental, crossover study with repeated-measures analysis Methods: Thirty-eight recreational skiers completed a single-leg postural balance test while wearing standardized ski boots in their unmodified state (control), and with medial and lateral canting wedges applied. Kinematics, kinetics, postural control measures, and neuromuscular activity of the lower extremity were assessed using optical motion capture, instrumented force plates, and electromyography. Results: Canting modifications had significant impact on lower extremity kinematics and kinetics: canting wedges on the medial side of the foot significantly decreased knee valgus moments, hip internal rotation, and hip adduction. Medial canting also improved some postural control measures associated with balance quality, and reduced activation levels of the Vastus Lateralis, Biceps Femoris, and Tibialis Anterior. Conclusions: In the laboratory setting, canting appears to be an appropriate option for improving balance in alpine skiers. Medial canting can alter skier kinematics and kinetics in ways which are consistent with mechanisms of ACL injury. Canting may also result in reduced neuromuscular effort. These changes in movement have potential to prevent lower limb injuries in alpine skiers. The findings of this study motivate future research to predict individual responses to canting treatment in a study setting more closely resembling the sports environment.